Global estimates on the number of people blind or visually impaired by diabetic retinopathy: a meta-analysis from 1990 to 2010 - Leasher, Janet L.; Jonas, Jost B. (Diabetes care, 2016)
OBJECTIVE: To estimate global and regional trends from 1990 to 2010 of the prevalence and number of persons visually impaired specifically by diabetic retinopathy (DR), as a complication of the precipitous trends in global diabetes, is fundamental for health planning purposes. RESEARCH DESIGN AND METHODS: The meta-analysis of published population studies from 1990 to 2012 for the Global Burden of Disease Study 2010 (GBD) yielded estimated global regional trends in DR among other causes of moderate and severe vision impairment (MSVI; presenting visual acuity <6/18, ≥3/60) and blindness (presenting visual acuity <3/60). RESULTS: Globally in 2010, out of overall 32.4 million blind and 191 million visually impaired people, 0.8 million were blind and 3.7 million were visually impaired because of DR, with an alarming increase of 27% and 64%, respectively, spanning the two decades from 1990 to 2010. DR accounted for 2.6% of all blindness in 2010 and 1.9% of all MSVI worldwide, increasing from 2.1% and 1.3%, respectively, in 1990. These figures were lower in regions with younger populations (<2% in East and Southeast Asia and Oceania) than in high-income regions (North America, Western Europe, and Australasia) with relatively aging populations (>4%). CONCLUSIONS: The number of persons with visual impairment due to DR worldwide is rising and represents an increasing proportion of all blindness/MSVI causes. Age-standardized prevalence of DR-related blindness/MSVI was higher in sub-Saharan Africa and South Asia. One out of 39 blind people had blindness due to DR, and 1 out of 52 visually impaired people had visual impairment due to DR.